Aerodynamic performance of MAV wing with fuselage and stabilizer \ Muhammad Izzuddin Arif Abdul Samad - Abdul Samad, Muhammad Izzuddin Arif (2017)
The history of micro air vehicles (MAVs) really began with the development of model airplanes in the 19th century. However, the study of micro air vehicles (MAVs) is currently lack with the understanding of aerodynamics for the small aircraft flying at low speeds. Based on previous findings, the study on Zimmerman and Inverse Zimmerman wings had only focus on the wing performances rather than a complete MAV configuration, which exclude the fuselage and stabilizer components. Thus, the objective of current study is to find the discrepancy in aerodynamic performances between the MAV wing by including the fuselage and stabilizer components. In this study, the Zimmerman and Inverse Zimmerman wing with fuselage and stabilizer configuration is known as ZWFS and IZWFS, respectively. While the wing only configurations (without fuselage and stabilizer) are known as ZW and IZW. In the present research, CFX simulation method is used to study the performance on all wings. To solve the turbulent flow issue, 3D RANS equations coupled with SST k-ro turbulent equation are employed in the simulation works. Based on the simulation results, the wing only configurations (ZW and IZW) induce higher CL magnitude (between 42%-61%) compared to wing-fuselage configuration (ZWFS and IZWFS). However in CD performance, ZW induced better CD distribution than others configuration. The fuselage and stabilizer components induced a slight disadvantage (about 12.4%) in overall CD distribution. In CM performances, IZWFS have better CM than IZW by 0.54% which indicates that the wing with fuselage and stabilizer induced better stability. Moreover, in CL/CD analysis, the result shows that the wing only configuration (ZW and IZW) have better CL/CD distribution (between 39%-52%) compared to IZWFS and ZWFS. The TV studies also reveal that the benevolent CD performance on IZWFS is due to larger TV formations found on the wing. While, the low pressure distribution (CP) study reveals that IZW have more concentrated -Cpmin at the wing tips of the design which make IZW have better CL performance than ZW, ZWFS and IZWFS.